Evaluation of a microfluidic flow assay to screen for von Willebrand disease and low von Willebrand factor levels. (23rd November 2017) - Lehmann, M.; Ashworth, K.; Manco‐Johnson, M.; Di Paola, J.; Neeves, K. B.; Ng, C. J.
Abstract : Essentials von Willebrand factor (VWF) function is shear stress dependent. Platelet accumulation in a microfluidic assay correlates with VWF levels. The microfluidic assay discriminates type 1 von Willebrand disease from healthy controls. The microfluidic flow assay detects responses to therapeutic intervention (DDAVP). Summary: Background: von Willebrand disease (VWD) is a mucocutaneous bleeding disorder with a reported prevalence of 1 in 10 000. von Willebrand factor (VWF) function and platelet adhesion are regulated by hemodynamic forces that are not integrated into most current clinical assays. Objective: We evaluated whether a custom microfluidic flow assay (MFA) can screen for deficiencies in VWF in patients presenting with mucocutaneous bleeding. Methods: Whole blood from individuals with mucocutaneous bleeding was assayed in a custom MFA. Results: Thirty‐two patients with type 1 VWD (10/32) or reported mucocutaneous bleeding were enrolled. The platelet adhesion velocity ( r = 0.5978 for 750 s −1 and 0.6895 for 1500 s −1 ) and the maximum platelet surface area coverage ( r = 0.5719 for 750 s −1 and 0.6633 for 1500 s −1 ) in the MFA correlated with VWF levels. Furthermore, the platelet adhesion velocity at 750 s −1 (type 1 VWD, mean 0.0009761, 95% confidence interval [CI] 0.0003404–0.001612; control, mean 0.003587, 95% CI 0.002455–0.004719) and at 1500 s −1 (type 1 VWD, mean 0.0003585, 95% CI 0.00003914–0.0006778; control, mean 0.003132, 95% CI 0.001565–0.004699) differentiated type 1 VWD from controls. Maximum platelet surface area coverage at 750 s −1 (type 1 VWD, mean 0.1831, 95% CI 0.03816–0.3281; control, mean 0.6755, 95% CI 0.471–0.88) and at 1500 s −1 (type 1 VWD, mean 0.07873, 95% CI 0.01689–0.1406; control, mean 0.6432, 95% CI 0.3607–0.9257) also differentiated type 1 VWD from controls. We also observed an improvement in platelet accumulation after 1‐desamino‐8‐d ‐arginine vasopressin (DDAVP) treatment at 1500 s −1 (pre‐DDAVP, mean 0.4784, 95% CI 0.1777–0.7791; post‐DDAVP, mean 0.8444, 95% CI 0.7162–0.9726). Conclusions: These data suggest that this approach can be used as a screening tool for VWD.